2014
DOI: 10.1515/cclm-2014-0350
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and thyroid autoimmunity in apparently healthy pregnant and non-pregnant Mexican women

Abstract: Laboratory evidence of AITD is common in this population of Mexican pregnant and non-pregnant women. TFT results and reference intervals are influenced by pregnancy and thyroid autoimmunity. For optimal interpretation of TFT results, gestational age-specific reference intervals established using a local patient population should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The American Thyroid Association [16] has proposed that reference ranges for free T4 during pregnancy should be established for each specific population and trimester of pregnancy, in samples of women without thyroid disease, without thyroid antibodies and with adequate iodine consumption. Following these criteria, in Mexico, we only have found a study conducted in Yucatan [39] which established a reference range for the first trimester from 0.75 to 1.7 ng/dL, not far from the range proposed by our laboratory (0.76 to 2.24 ng/dL). A recent study including Mexican pregnant women without history of thyroid disease, reported that the prevalence of isolated hypothyroxinemia was 12.8%; however, the whole frequency of thyroid disorders was 46.7% [40]; this suggests that prevalence of thyroid disorders during pregnancy in Mexico, could be greater than that reported by literature.…”
Section: Discussionmentioning
confidence: 86%
“…The American Thyroid Association [16] has proposed that reference ranges for free T4 during pregnancy should be established for each specific population and trimester of pregnancy, in samples of women without thyroid disease, without thyroid antibodies and with adequate iodine consumption. Following these criteria, in Mexico, we only have found a study conducted in Yucatan [39] which established a reference range for the first trimester from 0.75 to 1.7 ng/dL, not far from the range proposed by our laboratory (0.76 to 2.24 ng/dL). A recent study including Mexican pregnant women without history of thyroid disease, reported that the prevalence of isolated hypothyroxinemia was 12.8%; however, the whole frequency of thyroid disorders was 46.7% [40]; this suggests that prevalence of thyroid disorders during pregnancy in Mexico, could be greater than that reported by literature.…”
Section: Discussionmentioning
confidence: 86%
“…The studies included a total number of 132,794 pregnant women, comprising 68,097 samples analysed by Abbott (14 studies), 15,164 by Beckman (9 studies), 30,903 by Roche (15 studies) and 21,819 by Siemens (11 studies). Nineteen studies excluded women with antibodies to either thyroid peroxidase (TPOAb) or thyroglobulin (TgAb), 13,14,1720,22,31,33,34,36,39,41,44,45,47,51,52,55 while 24 studies did not measure TgAbs and excluded women with positive TPOAb only. 15,16,21,2325,2730,32,35,37,38,40,42,43,46,4850,53,54 The median age of patients ranged from 24 to 35 years with TSH and FT4 reference intervals determined during the first, second and third trimesters in 42, 28 and 26 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we searched for recent reports on screening studies of TgAb and TPOAb. To avoid the influence of diseases themselves, we only considered studies done on healthy control subjects in various regions in different countries [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In healthy subjects, the incidence of positive TgAb or TPOAb is …”
Section: Discussionmentioning
confidence: 99%